Impact of Organizational Justice on Turnover Intentions: Moderating Role of Job Embeddedness - Sadia Arif (SEISENSE Journal of Management, 2018)
It is evident from the past research that employees who perceive the organizational policies as not just, the employees tend to leave the organizations and start their professional career in other organizations where they feel comfortable and organization policies as fair and just. Literature accords the moderate relationship of job embeddedness on turnover intentions. This study analyzed the moderate relationship of job embeddedness on turnover intentions and organizational justice in banking sector of Pakistan. Sample of study consists of 313 banking employees from different cadre. Regression Analysis was used to analyze the data. Results clearly indicate that job embeddedness do not moderate the relationship of turnover intentions and organizational justice. There is further need to explore the role of job embeddedness in other professional organizations. Implications for management and future directions are discussed.